Resting state functional connectivity differences between behavioral variant frontotemporal dementia and Alzheimer’s disease - Hafkemeijer, Anne; Möller, Christiane; Dopper, Elise G.; Jiskoot, Lize C.; Schouten, Tijn M.; van Swieten, John C.; van der Flier, Wiesje M.; Vrenken, Hugo; Pijnenburg, Yolande A.; Barkhof, Frederik; Scheltens, Philip; van der Grond, Jeroen; et al. (Frontiers in Human Neuroscience, 2015)
Alzheimer’s disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are the most common types of early-onset dementia. Here, we apply resting state functional magnetic resonance imaging (fMRI) to study functional brain connectivity differences between AD and bvFTD. We used resting state fMRI data of 31 AD patients, 25 bvFTD patients, and 29 controls. We studied functional connectivity throughout the entire brain, applying two different analysis techniques, studying network-to-region and region-to-region connectivity. A general linear model approach was used to study group differences, while controlling for physiological noise, age, gender, study center, and regional gray matter volume. Given gray matter differences, we observed decreased network-to-region connectivity in bvFTD between a) lateral visual cortical network and lateral occipital and cuneal cortex, and b) auditory system network and angular gyrus. In AD, we found decreased network-to-region connectivity between the dorsal visual stream network and lateral occipital and parietal opercular cortex. Region-to-region connectivity was decreased in bvFTD between superior temporal gyrus and cuneal, supracalcarine, intracalcarine cortex, and lingual gyrus. We showed that the pathophysiology of functional brain connectivity is different between AD and bvFTD. However, the group differences in functional connectivity are less abundant than has been shown in previous studies.